Bedell Smith and functionalist dilemmas - Urseth, Leif H. (Kansas State University, 2010)
General Walter Bedell Smith is the subject of this dissertation. It examines his career as Eisenhower's chief of staff from a functionalist perspective. Functionalism as a school of thought emphasizes the organic nature of social institutions, the importance of improvisation while framing solutions to problems, and the necessity of producing predictable results. In practice, the US Army and Smith applied functionalism in a restricted way, but conceived of the General Staff as the "brain of the army." While working for General Marshall in the War Department General Staff and later as General Eisenhower's chief of staff, General Smith met his responsibilities with respect to order, cohesion and objectives. Two general conditions complicated Smith's role at Eisenhower's headquarters: first, the burgeoning size of the staff made it difficult for Smith to manage by means of direct supervision and still preserve a measure of initiative among staff members; second, Smith's poor health and choler sometimes hindered his ability to adopt means that were consistent with the organic aspect of functionalism. In Washington, Algiers and London, Bedell Smith gained notoriety as a "hatchetman" who did his superior's dirty work. His ugly reputation was fitting in some ways, but undeserved in others. His achievements have been underestimated. Smith was the firm defender of the Eisenhower's prerogatives. Among British colleagues, he was a disciple of cooperation and diplomacy. He was intelligent, orderly and functionalist in the sense that his decisiveness and willingness to accept responsibility achieved quick and predictable results. Smith's understanding of principal issues and his grasp of details earned the trust and respect of colleagues. He acted out of duty, not "natural" meanness. The traits of a "hatchetman" - feared and detested by some - were the distinguishing features that won favor from his superiors, Marshall and Eisenhower.
Keywords: Functionalist, Dilemmas, Bedell; History, Modern (0582); History, United States (0337)